Correlation between Level of Soluble Suppression of Tumorigenicity-2 (sST2) with Global Longitudinal Strain (GLS) of Left Ventricle in Patients with Acute Myocardial Infarction - Dyah Adhi Kusumastuti; Nahar Taufiq; Hasanah Mumpuni (ACI (Acta Cardiologia Indonesiana), 2019)
Background: Epidemiological data show that the incidence of heart failure after myocardial infarction is about 20%. The incidence of heart failure after acute myocardial infarction is also known to increase post-infarct mortality. The incidence of heart failure is related to the remodelling process after acute myocardial infarction. The acute remodelling process after acute myocardial infarction involves a mechanical mechanism in which there is a change in left ventricular geometry as an adaptive response to the incidence of infarction and then results in increased left ventricular wall stress. Increased left ventricular wall stress can be assessed by measuring global longitudinal strain (GLS) using echocardiography. On the other hand, mechanical overload in the myocardium is known to increase sST2 levels. The relationship between increased levels of sST2 and left ventricular GLS in patients with acute myocardial infarction has never been studied before.Methods: An analytic observational study with a cross-sectional design conducted from July to September 2018 at Dr Sardjito Hospital. Patients diagnosed with acute myocardial infarction and fulfilling the inclusion and exclusion criteria were included in the study. Measurement of sST2 levels and echocardiographic examination was performed on the first day after admission. Correlation test analysis was conducted to determine the relationship between sST2 levels and left ventricular GLS.Results: There were 72 subjects, with 62 STEMI subjects and 10 NSTEMI subjects. The mean level of sST2 in this study was 4,252 ± 198 pg / mL. Measurement of the left ventricular function obtained a mean ejection fraction of 47 ± 9%, LVIDd 45.79 ± 6.2 mm and GLS values of -9.3 ± 3.3%. Correlation test using Spearman test showed that there was no correlation between increased sST2 levels and decreased GLS values in patients with acute myocardial infarction (r = -0.133; p = 0.344).Conclusion: Increased sST2 levels were not correlated with decreased GLS values in patients with acute myocardial infarction.